Research on Body Type Correction of FINA Diving Difficulty Coefficient Based on Rigid Body System - Su Zhang; Wen Xiang; Guozhong Zou (Complexity)
In order to reduce the influence of athlete’s body shape on the difficulty coefficient of diving, a more reasonable calculation method of body shape correction coefficient is proposed based on the original calculation rules of diving difficulty coefficient. First, the composition of the original diving difficulty coefficient and influencing factors is analyzed and the relationship between the various structural parts is fully clarified. Second, a coupled nonrigid body dynamics model is established and a 2-body model is used to simulate complex diving actions, and it is concluded that diving time is positively correlated with body shape. Finally, the air movement part and the water entry part of diving are discussed separately, the calculation model of the difficulty coefficient of body shape correction is established, and the original difficulty coefficient is corrected. The results show that the difficulty coefficient of each movement is obviously increased. This effectively avoids the influence of body shape on the diving difficulty coefficient.